Supramolecular Nanoscaffolds within Cytomimetic Protocells as Signal Localization Hubs - Magdalena Estirado, Eva; Mason, Alexander F; Alemán García, Miguel Ángel; van Hest, Jan C M; Brunsveld, Luc (Journal of the American Chemical Society, 2020)
The programmed construction of functional synthetic cells requires spatial control over arrays of biomolecules within the cytomimetic environment. The mimicry of the natural hierarchical assembly of biomolecules remains challenging due to the lack of an appropriate molecular toolbox. Herein, we report the implementation of DNA-decorated supramolecular assemblies as dynamic and responsive nanoscaffolds for the localization of arrays of DNA signal cargo within hierarchically assembled complex coacervate protocells. Protocells stabilized with a semipermeable membrane allow trafficking of single-stranded DNA between neighboring protocells. DNA duplex operations demonstrate the responsiveness of the nanoscaffolds to different input DNA strands via the reversible release of DNA cargo. Moreover, a second population of coacervate protocells with nanoscaffolds featuring a higher affinity for the DNA cargo enabled chemically programmed communication between both protocell populations. This combination of supramolecular structure and function paves the way for the next generation of protocells imbued with programmable, lifelike behaviors.